Molecular screening of ADAMTSL2 gene in 33 patients reveals the genetic heterogeneity of geleophysic dysplasia. Issue 6 (17th March 2011) - Allali, Slimane; Le Goff, Carine; Pressac–Diebold, Isabelle; Pfennig, Gwendoline; Mahaut, Clémentine; Dagoneau, Nathalie; Alanay, Yasemin; Brady, Angela F; Crow, Yanick J; Devriendt, Koen; Drouin-Garraud, Valérie; Flori, Elisabeth; et al.
Abstract : Background: Geleophysic dysplasia (GD, OMIM 231050) is an autosomal recessive disorder characterised by short stature, small hands and feet, stiff joints, and thick skin. Patients often present with a progressive cardiac valvular disease which can lead to an early death. In a previous study including six GD families, we have mapped the disease gene on chromosome 9q34.2 and identified mutations in the A Disintegrin And Metalloproteinase with Thrombospondin repeats-like 2 gene ( ADAMTSL2 ). Methods: Following this study, we have collected the samples of 30 additional GD families, including 33 patients and identified ADAMTSL2 mutations in 14/33 patients, comprising 13 novel mutations. The absence of mutation in 19 patients prompted us to compare the two groups of GD patients, namely group 1, patients with ADAMTSL2 mutations (n=20, also including the 6 patients from our previous study), and group 2, patients without ADAMTSL2 mutations (n=19). Results: The main discriminating features were facial dysmorphism and tip-toe walking, which were almost constantly observed in group 1. No differences were found concerning heart involvement, skin thickness, recurrent respiratory and ear infections, bronchopulmonary insufficiency, laryngo-tracheal stenosis, deafness, and radiographic features. Conclusions: It is concluded that GD is a genetically heterogeneous condition. Ongoing studies will hopefully lead to the identification of another disease gene.